2011
DOI: 10.1159/000327989
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Serous Carcinoma of the Testis: A Case Report and Review of the Literature

Abstract: Serous tumours of the testis and paratestis are rare, with fewer than 50 cases reported in the literature. The majority of the reported cases have been borderline serous tumours, and these tend not to recur or metastasize. Conversely, serous carcinomas can metastasize but this is often a late event. The presence of invasion in an otherwise borderline tumour has also been associated with the development of metastatic disease several years later, thus highlighting the importance of extensive sampling of all case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Lp‐PLA2 exerts its activity through hydrolyzing oxidized phospholipids and decreasing generation of oxidized low‐density lipoprotein (oxLDL), and then affects the development of cardiovascular disease . In recent years, the link between Lp‐PLA2 gene polymorphism and stroke, particularly ischemic stroke, is investigated in several studies . Hiramoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lp‐PLA2 exerts its activity through hydrolyzing oxidized phospholipids and decreasing generation of oxidized low‐density lipoprotein (oxLDL), and then affects the development of cardiovascular disease . In recent years, the link between Lp‐PLA2 gene polymorphism and stroke, particularly ischemic stroke, is investigated in several studies . Hiramoto et al .…”
Section: Introductionmentioning
confidence: 99%
“…So that we can address this question, we reviewed the literature on serous tumours of the testis, and identified 38 neoplasms . In contrast to the ovary, where high‐grade tumours represent the most common type, we found that 22 of the testicular neoplasms showed features of borderline serous tumour, and five of the remaining invasive neoplasms contained borderline areas, consistent with low‐grade serous carcinoma.…”
Section: Acknowledgementsmentioning
confidence: 96%
“…So that we can address this question, we reviewed the literature on serous tumours of the testis, and identified 38 neoplasms. [5][6][7][8][9][10][11][12][13][14] In contrast to the ovary, where high-grade tumours represent the most common type, we found that 22 of the testicular neoplasms showed features of borderline serous tumour, and five of the remaining invasive neoplasms contained borderline areas, consistent with low-grade serous carcinoma. Unfortunately, none of the reports on the remaining 11 invasive neoplasms mentioned whether the tumour was low or high grade, but they showed a relatively indolent behaviour, with only two cases reported to have developed distant metastases.…”
Section: © 2014 John Wiley and Sons Ltdmentioning
confidence: 99%
“…Serous carcinomas are characterized by stromal invasion, which can be recognized by the presence of desmoplastic response, isolated papillae within artifactual clear spaces, or a solid pattern of neoplastic proliferation (Figure 1c) [3,36]. There often is an associated component of SBT, which is rarely observed in ovarian serous carcinomas and only in the context of low-grade serous carcinomas, which comprise only approximately 5% of ovarian serous cancers [36,45,46,62]. Therefore, this frequent association of borderline differentiation with serous carcinoma in the testis suggests that low-grade carcinomas may make up a much larger proportion-if not virtually all-of the reported cases of serous carcinomas of the testis, a characteristic that is in stark contrast to ovarian carcinomas.…”
Section: Serous Tumorsmentioning
confidence: 99%
“…Generally, the clinical course of benign and borderline serous tumors is very favorable, with no reports of recurrence or metastasis following complete orchiectomy. Prognosis for serous carcinoma is more guarded, with reports of metastatic disease to the lymph nodes, peritoneum, lungs, adrenal glands, and leptomeninges [37][38][39][40]45]. Overall, metastasis occurred in 26% of reported serous carcinoma cases, and death from disease followed in half of those cases.…”
Section: Serous Tumorsmentioning
confidence: 99%